Prevention of Transboundary Spread of Pests and Pathogens is Enhanced with Farmer’s Support - Kumari, Safaa (Food and Agriculture Organization of the United Nations, 2022)
More than 1,300 pests and pathogens threaten crops globally, with an estimated economic impact of around $540 billion annually. The severe damage inflicted by introduced pests and pathogens represents a serious threat to food systems and biodiversity. Unregulated germplasm transfers and exchanges have been recognized as an essential pathway for spreading pests and pathogens through human collection and distribution activities (moving pests between geographies and introducing them into new regions where they did not exist before). The spread of pests has increased dramatically in recent years through the agricultural trade and unintentional movement of infected living materials (e.g. infected seed, tissue culture materials), climatic factors (e.g. wind, rainfall), and insect or other vectors. Therefore, extreme care is required to ensure that the exchanged germplasm is pest-free. The Consortium of International Agricultural Research Centers (CGIAR) have established Germplasm Health Units (GHUs) to guarantee the safe movement of plant materials, along with compliance with the International Plant Protection Convention (IPPC) procedures and the International Standards for Phytosanitary Measures (ISPMs) applied by National Plant Protection Organizations (NPPOs) to prevent the introduction and control the spread of pests along with plants or plant products. To safeguard countries from quarantine risks (e.g. transmission of insect pests, pathogens and weeds) associated with the movement of germplasm, ICARDA’s GHUs follow a regulatory and quarantine program working in close collaboration with competent institutions where ICARDA has platforms for crop breeding, germplasm multiplication, evaluation and genetic resources. ICARDA’s GHUs are responsible for the monitoring, clearance and documentation of safe germplasm movement at the center, and share the updated technology with NPPOs in the host countries and farmers. To produce high-quality and healthy seed, farmers should apply the following practices at different crop stages: (i) before planting, planting in regions with minimum disease pressure, properly applying crop rotations, using certified seed, avoiding local or unknown seed sources, etc.; (ii) during crop establishment, undertaking field inspections to eradicate infected plants as soon as observing abnormal symptoms, applying pesticides at the most appropriate timing to prevent pest emergence, implementing weed control, etc.); and (iii) at the end of the season, using good harvesting machines and seed cleaning techniques, applying fumigation, ensuring good storage conditions, etc.). Additionally, farmers should be encouraged to collaborate by delivering samples for testing, from their fields and harvested materials, to the official authorities at the end of the season. In the case of detecting new emerging pests, it is the farmer’s responsibility to notify NPPOs of any unusual symptoms or signs in the field, and they should follow the instructions of NPPOs, especially in case of eradication. Moreover, trading infected seed and keeping them as planting material for the next season should be prohibited. The farmer is the connector between the plant and NPPOs to identify any unknown symptoms or signs in the field, conduct regular field visits to observe the plant health status, and take action in case of any invasive new pest. To ensure reports from farmers on pest outbreaks are as timely, honest and transparent as possible, proper communication channels and support mechanisms (i.e. lowering the economic loss in case of yield losses due to pest outbreaks) need to be put in place, establishing a sense of collaboration.